Analisis Pendapatan Usaha Tani Bawang Merah Di Desa Tolok Satu Kecamatan Tompaso Kabupaten Minahasa - Wowiling, Dewi A. V.; Maweikere, Audrey Julia Maria; Benu, Noortje Marsellanie (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
The purpose of this study was to analyze the income of shallot farming in Tolok Satu Village, Tompaso District, Minahasa Regency. This research was conducted for 3 months, namely December to February 2023. The methods used in this study are primary and secondary, primary data obtained at the research site, namely to the shallot farmers of Tolok Satu Village with direct interview techniques to farmers using a list of questions (questionnaires) in data collection, secondary data obtained from related agencies, the population in this study amounted to 23 people. The results of the research were analyzed by analyzing costs, revenues, revenues, continued with the Revenue Cost Ratio (R / C). The results of shallot farming research in Tolok Satu Village show the total average shallot production costs per planting season of Rp.11,231,930. Total shallot farming receipts per planting season of Rp.35,700,000. Net income of shallot farming of Rp.24,468,070. R / C Ratio of shallots in Tolok Satu Village is 3.1 which means that farming is profitable.